Pendapat Stakeholder Tentang Kesyariahan Produk-Produk Financial Derivative - Kurniawan, Doni; Laila, Nisful (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The purpose of this study is Knowing and explaining how comments fromÂ stakeholders regarding sharia product of derivatives markets and how the mechanism, asÂ well as to Knowing whether the derivatives market activity is growing rapidly both to theÂ individuals who are involved in it and outside it can arouse the hearts of the people ofÂ the opinion sharia and their impact on the Indonesian economy system orderThis study used qualitative methods, dhelpimethod , namely by conducting interviewsÂ to stakeholders consisting of practitioners , academics , expert in jurisprudence , andÂ representatives from the community . Supporting data obtained from the articles on theÂ derivatives market , a book about the derivatives market , the internet , journals , andÂ relevant parties in the field.Â Results from this study is that of the third -party stakeholders , consisting of,Â practitioners , academics , and jurists , found in derivative transactions may be declared, and the opinion of the academics that derivative transactions including greetingsÂ âMaghribâ ( maiysir , gharar , riba )